Book review: Barnes, M., Brannelly, T., Ward, L., Ward, N. (2015). Ethics of care: Critical advances in international perspectives. Policy Press. 286pp, ISBN: 9781447316541 - Richard Ingram (Scottish Journal of Residential Child Care)
This edited volume provides a comprehensive conceptual and practical exploration of ethics of care from a diverse range of perspectives and contexts. The market place for such a book in not over-crowded and this allows the editors to rightly lay claim to a book that forges new ground in terms of the relevance and applicability of ethics of care globally and across professions. The book is helpfully split into two focussed sections: theoretical developments and practical applications.